2018
DOI: 10.1371/journal.pone.0192873
|View full text |Cite
|
Sign up to set email alerts
|

Critical domain interactions for type A RNase P RNA catalysis with and without the specificity domain

Abstract: The natural trans-acting ribozyme RNase P RNA (RPR) is composed of two domains in which the catalytic (C-) domain mediates cleavage of various substrates. The C-domain alone, after removal of the second specificity (S-) domain, catalyzes this reaction as well, albeit with reduced efficiency. Here we provide experimental evidence indicating that efficient cleavage mediated by the Escherichia coli C-domain (Eco CP RPR) with and without the C5 protein likely depends on an interaction referred to as the "P6-mimic"… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 54 publications
3
14
0
Order By: Relevance
“…The modular architecture of large ribozymes, such as bacterial RNase P ribozymes and group I ribozymes, is an important feature in ribozyme biochemis-the S-domain retained residual catalytic activity. [27,28] To address the ribozyme activity of the B-type C-domain RNA, an in vitro evolution experiment was also performed, [29] in which RNA sequences were successfully identified to serve as artificial substrates for the C-domain RNA from B. subtilis RNase P.…”
Section: Modular Organization Of Bacterial Rnase P Ribozymesmentioning
confidence: 99%
“…The modular architecture of large ribozymes, such as bacterial RNase P ribozymes and group I ribozymes, is an important feature in ribozyme biochemis-the S-domain retained residual catalytic activity. [27,28] To address the ribozyme activity of the B-type C-domain RNA, an in vitro evolution experiment was also performed, [29] in which RNA sequences were successfully identified to serve as artificial substrates for the C-domain RNA from B. subtilis RNase P.…”
Section: Modular Organization Of Bacterial Rnase P Ribozymesmentioning
confidence: 99%
“…Structural information of both bacterial A-type and B-type RPRs reveals that RPR consists of two independently folded domains, the catalytic domain (C-domain) and the specificity domain (S-domain), which play key roles in substrate cleavage and substrate binding, respectively 6–11 . It has been found that bacterial RPR even the C domain alone possesses catalytic activity under high ionic strength condition or in the presence of spermidine in vitro 12,13 . But the sole protein subunit RPP is essential for enhancing the efficiency and fidelity of substrate recognition and cleavage under physiological conditions 1419 .…”
Section: Introductionmentioning
confidence: 99%
“…This suggested electrostatic repulsion effects between enzyme and substrate RNAs upon disruption of the L18-P8 contact. Kirsebom and coworkers probed Eco WT and mL18 (5'-CUUG) P RNA with Pb 2+ ions and RNase T1 (Mao et al, 2018). They observed structural changes in P11 and at the junction between P14 and P11 in the S-domain of the mL18 mutant RNA with disrupted L18-P8 interaction.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there was a change in RNase T1 susceptibility at helix P5 in the C-domain, close to the active site. Generally, higher Pb 2+ concentrations were required for the mL18 versus WT P RNA to induce backbone hydrolysis at high affinity metal ion binding sites (Mao et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation